(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Obstructive sleep apnea is a common sleep disorder caused by a partial or complete collapse of the upper airway due to a shift of soft tissues. A parameter to measure the airway collapsibility is the critical closing pressure, which defines the pharyngeal pressure at which the airway collapses. A 3D printed collapsible model of an idealized upper airway geometry was used to perform deformation and pressure measurements and thus to determine the critical closing pressure. The influence of increasing airway resistance on the deformation behavior was examined by changing the size of the inflow area.